Evaluate and compare the antibacterial activity of lysine with curcumin and gold nanoparticles - Sheymaa S. Ismael,; Entesar Hussein Ali,; Iman Ismael Jabbar, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The misuse of antibiotics directly contributes to the emergence of drug-resistant microbes. Therefore, developing innovative therapeutic approaches is crucial for addressing this issue. The rapid advancement of nanotechnology provides hope that this problem can be resolved. Consequently, conventional methods are employed to synthesize and characterize the samples. The antibacterial activity of the lysine-curcumin combination, which is a lysine-capped gold nanoparticle, was evaluated against Staphylococcus aureus and Escherichia coli. Fourier-transform infrared spectroscopy (FTIR), melting point analysis, zeta potential measurement, and UV-visible spectroscopy were used in the synthesis and characterization of curcumin, lysine, and gold nanoparticles, as well as their combinations (lysine-gold and lysine-co-curcumin). The agar-well diffusion method examined the samples' antibacterial activities against S. aureus and E. coli. Curcumin showed notable effectiveness against S. aureus, with inhibitory zones of up to 15 mm at 100% concentration. It shows less efficacy against E. coli (5 mm at 100% concentration). Lysine had significant efficacy against S. aureus (8 mm at 100%) but no effect on E. coli (4 mm at 50% and 100%). The antibacterial activity of gold nanoparticles was found to be moderate against S. aureus (10 mm at 100%) and restricted against E. coli (2 mm at 100%). Remarkably, the combination of lysine and gold nanoparticles enhanced antibacterial effectiveness, resulting in inhibition zones of 14 mm for S. aureus and 8 mm for E. coli at 100%. Similarly, Lysine-Co-Curcumin exhibited high activity against S. aureus (14 mm at 100%) and E. coli (6 mm at 100%).